LANGKAH INDONESIA DALAM MENGATASI KEBIJAKAN BEA MASUK ANTI DUMPING TINGGI TERKAIN EKSPOR BIODIESEL KE UNI EROPA TAHUN 2017 - Wan Fadli Akbar; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The objective of this research is to understand Indonesia's Steps to Facing theEU's Demands for Indonesia's Biodiesel Disposal in 2013. Indonesia is the world'sleading biofuel exporter, even 90% of EU biodiesel imports from Indonesia.However, the EU claims that Indonesia has sold biodiesel to EU members at a pricebelow their normal value. According to EU investigations, the imposition ofadditional import duties for biodiesel industry in the European Union has beenimpaired by biodiesel imports from Indonesia and ArgentinaThis research is theoretically created by taking into account Liberalism'sperspective on International Relations and is supported by Adam Smith's AbsoluteExcellence theory. The formulation of all the theoretical arguments, facts, andframeworks in this study is guided by qualitative explanatory methods. The techniquein this research is through literature study. Data are obtained and collected fromjournal books, the last thesis and then from the internet related to the problem.Researchers found that Indonesia's Step Facing EU Demands Against DumpingIndonesian Biodiesel Product In 2013 through EU lawsuit to World TradeOrganization. Indonesia demanded the European Union through the World TradeOrganization (WTO) secretariat on June 10, 2014 and requests for consultationswith the WTO's Dispute Settlement Agency (DSB) as a third party. The governmentthrough the Ministry of Trade also sent a letter of objection to the European Unionon the decision. A letter of objection will be sent to the embassy in Jakarta. The letterwill be delivered by the government through the Ministry of Trade.Keywords: EU, Dumping Practice, Indonesia, Biodiesel